Pengaruh Jarak Tempuh ke Sekolah terhadap Motivasi Belajar Siswa di SMP Negeri 2 Sajingan Besar - Yohana, Yohana; Anasi, Putri Tipa; Harjanti, Diah Trismi; Wiyono , Hadi (Jurnal Pendidikan Geografi Undiksha, 2025)
This research seeks to ascertain the distance from students' residences to SMP Negeri 2 Sajingan Besar, evaluate the learning motivation of students at the institution, and investigate whether the distance travelled to school affects their motivation to study at SMP Negeri 2 Sajingan Besar. This study employs quantitative research methodologies, namely descriptive research and simple random sampling, with a total of 150 student respondents. Data analysis reveals that among 150 student respondents, 115 are categorised as short-distance commuters and 35 as long-distance commuters. Additionally, the learning motivation of students at SMP Negeri 2 Sajingan Besar is assessed at 81%, indicating a fairly strong level of motivation . Through the T test with sig results. 0.000 < 0.05 which shows that there is quite a significant influence between the distance students travel to school and students' learning motivation at SMP Negeri 2 Sajingan Besar. Therefore, teachers must strive to maintain and increase student learning motivation.